Vascular Neoplasms With NFATC1/C2 Gene Alterations : Expanding the Clinicopathologic and Molecular Characteristics of a Distinct Entity - Dashti, Nooshin K; Perret, Raul; Balzer, Bonnie; Naous, Rana; Michal, Michael; Dermawan, Josephine K; Antonescu, Cristina R (The American journal of surgical pathology, 2024)
Despite significant advances in their molecular pathogenesis, skeletal vascular tumors remain diagnostically challenging due to their aggressive radiologic appearance and significant morphologic overlap. Within the epithelioid category and at the benign end of the spectrum, recurrent FOS/FOSB fusions have defined most epithelioid hemangiomas, distinguishing them from epithelioid hemangioendothelioma and angiosarcoma. More recently, the presence of EWSR1/FUS :: NFATC1/2 fusions emerged as the genetic hallmark of a novel group of unusual vascular proliferations, often displaying epithelioid morphology, with alternating vasoformative and solid growth, variable atypia, reminiscent of composite hemangioendothelioma. In this study, we further our understanding and morphologic spectrum of NFATC -fusion positive vascular neoplasms by describing 9 new cases, including soft tissue locations and novel fusion partners. Combining with the initial cohort of 5 cases, a total of 14 patients were analyzed, showing slight female predilection and an age range of 10 to 66 (mean 42 y). Twelve patients had solitary lesions, while 2 had multifocal polyostotic (pelvic bones) disease. Overall, 12 lesions were intra-osseous and 2 in soft tissue. By targeted RNA Fusion panels or FISH, there were 6 cases of EWSR1::NFATC1 , 4 EWSR1::NFATC2 , 2 FUS::NFATC2 , 1 EWSR1 rearrangement, and 1 with a novel FABP4::NFATC2 fusion. Follow-up was available in 4 patients. One patient experienced 2 local recurrences, 11 and 15 years postdiagnosis, and one patient experienced progressive disease despite multimodality treatment (curettings, embolization, radiation) over 3 years. In summary, our extended investigation confirms that NFATC -related fusions define a distinct group of vascular neoplasms with variable architecture, epithelioid phenotype, and cytologic atypia, commonly located in the bone, occasionally multifocal and with potential for local recurrence and aggressive behavior but no metastatic potential. Molecular analysis is recommended in diagnostically challenging cases with atypical histology to exclude malignancy.
Keywords: vaskulární nádory; epiteloidní hemangioendoteliom; transkripční faktory; transkripční faktory NFATC; Vascular Neoplasms; hemangioendoteliom; NFATC Transcription Factors; ženské pohlaví; Humans; Hemangioendothelioma; hemangiom; Female; Transcription Factors; Hemangioendothelioma, Epithelioid; lidé; Hemangioma